Identifikasi Faktor Penyebab Ketidaksesuaian Pelaksanaan Retensi Dokumen Rekam Medik Inaktif di RS Husada Utama Kota Surabaya - Dwi Winda Agustin; Rossalina Adi Wijayanti; Gilang Nur Permana (Politeknik Negeri Jember, 2020)
Hospitals as a health service facility are required to make medical records Retention is the transfer of inactive DRM to inactive filing to reduce the amount of DRM that is on an active filing rack. The number of visits in the Husada Utama Hospital in Surabaya each year has increased that is not proportional to the large capacity of storage space, causing an incompatibility of the implementation of medical record document retention SOP. The purpose of this study was to identify problems using five elements of management namely man, money, method, material, machine. This research is a type of qualitative research. The results of this study are the identification of problems that occur and the causes of the problem are knowledge, education, training, operational costs, inactive storage space, medical record shelves, scanning equipment, computers and SOP. As a result of these problems will result in a buildup of medical record files which causes narrowing in the storage room that affects the hospital's accreditation standards. The alternative solutions to problems are the existence of SOP socialization, attending training, the existence of a budget for procurement of equipment, the expansion of storage space and the addition of medical record file shelves, the provision of scanning tools and computers as well as SOP evaluation.